Mycobacterium tuberculosis combine with EBV infection in severe adult meningoencephalitis: a rare case reports and literature review - Li, Mengjiao; Zhu, Junchi; Cheng, Lijuan; Kong, Ping (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundTuberculous meningitis (TBM) with adults Epstein-Barr (EB) virus encephalitis is a very rare infectious disease, with a high mortality and disability. Metagenomic next-generation sequencing (mNGS) of cerebrospinal fluid (CSF) is highly diagnostic. We report on a case of severe meningoencephalitis caused by co-infection with mycobacterium tuberculosis and EB virus. Brain MRI indicated a parenchyma lesion in the brain. mNGS of CSF indicated Mycobacterium tuberculosis and EB virus amplification, positive serum EB virus IgG antibodies, and improved symptoms after anti-tuberculosis and antiviral treatment. A re-examination of the brain MRI revealed that the significantly absorption of the lesions.Case reportA 49-year-old male patient presented with a chief complaint of headache and fever with consciousness disturbance. The brain magnetic resonance imaging showed a lesions in the right parenchymal brain with uneven enhancement, accompanied by significantly increased intracranial pressure, elevated CSF cell count and protein levels, as well as notably decreased glucose and chloride levels. mNGS of CSF showed the coexistence of Mycobacterium tuberculosis and EBV. The patient was diagnosed as TBM with EBV encephalitis. The patient’s symptoms gradually improved with the active administration of anti-tuberculosis combined with antiviral agents, the use of hormones to reduce inflammatory reaction, dehydration to lower intracranial pressure, and intrathecal injection. Subsequent follow-up brain magnetic resonance imaging indicated significant absorption of the lesions, along with a marked decrease in CSF count and protein levels, as well as obvious increase in glucose and chloride levels.ConclusionTBM associated with adult EBV encephalitis is extremely rare. The disease’s early stages are severe and have a high fatality rate. A prompt and accurate diagnosis is particularly important. NGS of CSF is of great value for early diagnosis.